An in vitro comparison of resistance to second and third order archwire activations of three different varieties of esthetic brackets - Soumya Ajith; Ajith R Gowda; Prashant Babaji; S Shivaprakash; Kuldeep Dmello; Suresh S Kamble (Wolters Kluwer Medknow Publications, 2013)
Background: When ceramic brackets were introduced as an esthetic alternative to the stainless steel brackets, it was a step ahead in the use of esthetic appliances for orthodontic treatment. Although ceramic brackets had overcome the drawbacks of the initial polycarbonate brackets such as staining and bracket slot distortion, they posed an altogether different problem. This was on account of the physical properties of the ceramic material, namely brittleness. Purpose of the Study: The purpose of this study is to investigate the physical properties of three different varieties of esthetic brackets, i.e., "MXI" ceramic bracket, "Spirit MB" bracket (Ormco), a composite bracket with metal slot reinforcement and the third one fiber bracket, with silicious copolymer, Natura (Leone Co.). Aims and Objective of the Study : The objective of this study is to compare the torsional resistance of the brackets and resistance of brackets to second order archwire activations. Conclusion: The strength of the selected brackets was more than sufficient to withstand orthodontic load without any fracture or deformation.